2006
DOI: 10.1111/j.1440-1797.2006.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biochemical, haematological and volume parameters in two treatment schedules of nocturnal home haemodialysis

Abstract: The authors conclude that NHHD6 offers the optimum biochemical, volume and clinical outcome, but NHHD3.5 has additional appeal to providers seeking home-based therapy cost advantages and consumable expenditure control. A flexible dialysis programme should offer all the time and frequency options of NHHD but in particular, should support NHHD at a frequency sympathetic to the clinical rehabilitation and lifestyle aspirations of individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Little was published about the outcomes of NHHD with an alternate night schedule. In Australia, where NHHD on alternate night has been performed in some centers, there was no significant difference in hemoglobin level or erythropoietin requirement between NHHD performed 3.5 times per week (i.e., alternate night) and that performed six times per week …”
Section: Discussionmentioning
confidence: 96%
“…Little was published about the outcomes of NHHD with an alternate night schedule. In Australia, where NHHD on alternate night has been performed in some centers, there was no significant difference in hemoglobin level or erythropoietin requirement between NHHD performed 3.5 times per week (i.e., alternate night) and that performed six times per week …”
Section: Discussionmentioning
confidence: 96%
“…Daily HD allows for increased clearance of middle‐molecules because of less rebound; and NHD increases middle‐molecule removal as a result of higher frequency and duration of HD. The relative increase in total solute removal with NHD is greatest for middle‐molecules such as phosphate and β2‐microglobulin, compared with small solutes such as urea and creatinine; and greater convective removal is also seen as a result of higher weekly ultrafiltration 42–45 . On conversion from conventional HD to NHD, one study reported serum β2‐microglobulin levels decreased from 27.2 to 13.7 mg/dL after 9 months with an increase in β2‐microglobulin mass removal from 127 to 585 mg 46 .…”
Section: Differences In Assessment Of Adequacymentioning
confidence: 99%
“…A prospective nonrandomized study of 11 patients on short daily, 12 patients on nocturnal, and matched controls receiving conventional hemodialysis for 5-36 months confirmed improvements in quality of life and bloodpressure control for both quotidian modalities and better phosphate control with nocturnal hemodialysis [10][11][12][13]. The main advantages of long intermittent hemodialysis are the favourable financial profile, the known improved hemodynamic benefits, and the increased middle molecule removal [4,7]. There is only limited use of quotidian incenter hemodiafiltration or home hemofiltration for both adults and children [14,15].…”
Section: Patient Selection and Modality Choicementioning
confidence: 90%
“…Despite some recent reports [7][8][9], there are no systematic studies comparing different forms of intensive hemodialysis. The advantages of quotidian nocturnal hemodialysis must be weighed against the requirement for long and frequent treatments, the potential for deficiency syndromes, long exposure to dialysis membranes and heparin, as well as night-time safety concerns.…”
Section: Patient Selection and Modality Choicementioning
confidence: 99%